The impact of a school-based physical activity program on children's movement behaviors, aerobic fitness and motor competence: a follow up study - Bloch, Moreno; Cordovil, Rita; Rodrigues, Luís P.; Martins, Clarice; Braga, Maria L.; Vale, Susana; Proença, Rui; Brito, João; Guilherme, José; Neto, Carlos; Seabra, André; Costa, Júlio A. (Frontiers in Sports and Active Living, 2025)
ObjectiveThis study evaluated the one-year impact of a 12-week school-based physical activity (PA) intervention, which added one extra hour of structured PA per week, on children's movement behaviors, aerobic fitness, and motor competence (MC).MethodsA longitudinal comparison between an experimental group (EG) and a control group (CG) was conducted at baseline (PRE), mid-intervention (DUR), post-intervention (POST), and one-year follow-up (FUP). The study was conducted in a single school without randomization. Movement behaviors (accelerometry), aerobic fitness (YYIR1C), and MC (MCA battery) were assessed. Due to school changes and parental noncompliance, the sample decreased from 38 to 23 participants (EG; n = 13; CG; n = 10), a 39% dropout rate.ResultsOne year post-intervention, the EG spent more time in moderate-to-vigorous PA (MVPA; + 41 min/day), less time in SED (−234 min/day), slept longer (+103 min/night), covered greater distances in the YYIR1C (+174 m), and achieved higher MC scores (+19% on the MCA battery test) compared to the CG. Although no significant differences in body weight were observed, the EG showed improved body mass index (BMI; −5 kg/m2) and a lower body fat percentage (−10%) when compared to the CG.ConclusionThe findings indicate that the benefits of a 3-month school-based PA intervention, which included an additional hour of physical education per week, can have sustained benefits for movement behaviors, physical fitness, and MC in children one year post-intervention. However, the small sample size and lack of randomization limit the generalizability of the results. Future research should employ larger, randomized trials to better assess the long-term impact of PA interventions on children’s health and fitness outcomes.